Essays in macroeconomics: public debt reform, progressive taxation and distributional effects of fiscal policy. - Carneiro, Fernando Moraes (2023)
This thesis is composed of three chapters devoted to study the effects of macroeconomic fiscal policies on economic growth and the distribution of income. The first chapter addresses the chronic fiscal imbalance of the Brazilian economy, which became more acute because of the fiscal efforts adopted to countervail the recessionary effects of the subprime crisis of 2008, the 2014-16 recession and, more recently, the COVID-19 pandemic. The study employs a dynamic general equilibrium model that distinguishes economic agents by their decision horizon and access to financial markets, and explores the dynamic effects of changes in fiscal mix and public debt consolidation strategies. The two types of households – Ricardians and non-Ricardians – correspond roughly to different income classes and the quantitative analysis assess the effects of these reforms on macroeconomic variables and welfare, leading to the conclusion that the distributive conflicts contribute to the lack of agreement with respect to the implementation of fiscal adjustments, and that this is a consequence of rational behavior of heterogeneous households. While the study targets the Brazilian economy, it can be also extended to other developing countries that experience similar fiscal challenges. Following, the second and the third chapters develop versions of an endogenous growth model with a progressive tax structure to investigate the tradeoff between economic growth and inequality. They are set up as dynamic general equilibrium models, and assume that the agents’ heterogeneity arises from differences in the intertemporal elasticity of substitution, rather than differences in the discount rate which is more often encountered in the literature. They show that the long-term equilibrium distributions of income and wealth are not degenerate, and that households that have higher willingness to substitute future for present consumption end up owning the largest fraction of the capital stock. In the second chapter, the model is calibrated to reflect a typical OECD country and considers a household disaggregation based on income quintiles, while the numerical simulations depict two complementary scenarios that evaluate the effects of tax reforms that eliminates the progressivity of the labor income tax but retains the progressivity of the capital income tax. The results show that increasing the progressivity of the tax on capital income reduces inequality faster and further than just eliminating progressivity on labor income without changing the tax on capital, although this effect comes at the expense of economic growth. The third chapter develops a version of the model where the tax code does not distinguish the sources of income, and the progressive tax is on total income, which is used to assess the effects of a reform that mimics the Tax Cuts and Jobs Act of 2017. The results reveal that such tax cut, which is financed by reducing the government consumption, boosts economic activity in the short run and sustain this growth during the transition, although lead to a slight increase in long-run inequality.